Aging effect of pH on the mechanical and tribological properties of dental composite resins. (3rd April 2018) - Wu, Tingting; Gan, Xueqi; Zhu, Zhuoli; Yu, Haiyang
ABSTRACT: This study evaluated the microhardness and wear behavior alterations of dental resins exposed to strong acid and alkaline degradation regimens. Fifty specimens of AP-X, Z350, P60, VITA ZETA and VITA LC resins were distributed into 10 groups. The control group was not subjected to aging treatment, while the other nine groups were assigned to the following pH solutions: 1, 7 or 13 for 1, 13 or 20 d, respectively. Vickers microhardness and wear behavior of materials without aging served as the reference. Repeated measurements were conducted for other specimens. Scanning electron microscopy was used to observe the morphology. Data were analyzed by repeated-measures one-way ANOVA, followed by the least significant difference (LSD) t-test ( P  ≤  0.05 ) for multiple comparisons. The aging process was aggravated over time. Alkaline medium significantly decreased the microhardness and wear resistance of resins, and led to serious surface damage. AP-X, P60 and Z350 immersed in different media showed a lower degradation than the nanoresin. The mechanical degradation of resin composites was aggravated with increased aging time. Strong alkaline media induced the largest reduction in mechanical and tribological properties. Hybrid resin composites with high filler loading exhibited better mechanical performance than nanoresins with low filler loading under different pH conditions.